Implementasi Pembelajaran Bahasa Inggris Berbasis Tematik Terpadu Bagi Siswa Sekolah Dasar - Meiliana Nurfitriani; Mohammad Fahmi Nugraha; Budi Hendrawan (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2021)
This study aims to determine how integrated thematic-based English learning is for elementary school students. The method used is a qualitative research method with descriptive analysis techniques with library research by examining the implementation of integrated thematic-based English learning for elementary school students. Data collection is done by reducing documents in the form of reports, news and research articles both nationally and internationally related to the topic of this research article. The results showed that the integration between student experience and previous knowledge possessed by children with English learning presented in a theme, will help children to gain knowledge, skills, and attitudes holistically. The theme developed is of course taking into account the children's knowledge, interests, and environment. Each skill in English is also not taught separately but is learned in an integrated manner with other skills. Therefore, the concept of learning English as a foreign language in accordance with the concept of an integrated thematic approach will be able to provide the value of knowledge, skills, and attitudes as a whole whose process is in line with the characteristics of children at the elementary school level.